ANALISIS PEMAHAMAN MASYARAKAT SUKU KAJANG TERHADAP PERCERAIAN DITINJAU DARI UU NO. 16 TAHUN 2019 - Syahrun Nur; Qadir Gassing; Musyfikah Ilyas (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
The main problem in this study is how the Kajang community understands about Law No. 16 of 2019 concerning marriage. Chapter VIII of marriage dissolution (divorce) with sub problems: 1) How is the knowledge of the Kajang Tribe Community in the practice of divorce adopted in Law No. . 16 of 2019? 2) How are the efforts of the Bulukumba Regency Religious Court in providing an understanding of Legal Divorce in terms of Law no. 16 of 2019? The type of research used is qualitative research with a normative theological approach, juridical and empirical law. Data collection methods consist of observation, interviews and documentation. The results or data obtained are then collected with three stages of data analysis including data reduction, data presentation, and drawing conclusions. The results of the study explain that some of the Kajang people already know about the divorce practice adopted in Law no. 16 of 2019. The Kajang Tribe community is able to know how the legal divorce practices adopted in Law no. 16 of 2019. Of course the position of Law no. 16 of 2019 has been used as a reference for the Kajang people in carrying out legal divorce practices. However, this must also be based on regulations and policies from customary law that applies in the Ammatoa Kajang Customary Area or commonly called Pasang ri Kajang. The efforts made by the Religious Court of Bulukumba Regency in providing understanding to the Kajang Tribe Community of Bulukumba Regency towards Legal Divorce are reviewed from Law no. 16 of 2019 is to carry out socialization and divorce assistance. The socialization aims to make the Kajang people understand about state legal regulations, especially for the legal process or practice of divorce. On the other hand, assistance is carried out because it is the duty and policy of the Religious Courts in providing guidance to the public regarding Law no. 16 of 2019 and the Kajang Tribe is no exception. The implications of the research include 1) It is hoped that it will be able to explain the extent to which the Kajang Tribe's understanding of Law no. 16 of 2019 concerning divorce in Tana Toa Village, Kajang District, Bulukumba Regency. 2) As material for the Bulukumba class II Religious Court and the Bulukmba Regency Government to give more and special attention to the Kajang Tribe community to be able to understand and know every applicable law, one of which is Law no. 16 of 2019 regarding divorce.